GURU MENURUT KITAB EFESUS - Eka Setyaadi; Sri Sulistyowati (Universitas Kristen Immanuel, 2024)
The background to writing this article was a shift in the meaning and appreciation of the teaching profession, specifically Christian Religious Education teachers. In this case, the author desires to provide a correct understanding of 'teachers' based on the concept of Biblical teaching, specifically according to the Book of Ephesians. Apart from that, the assessment of the teaching profession by Christian Religious Education teachers is starting to shift, a PAK teacher can become less proud or less confident in their profession. It is hoped that this article can make a positive contribution to PAK teachers themselves and to readers in general specifically in understanding and appreciating the PAK teacher profession. This research is pure library research, using descriptive methods, so that the research data is explanations or explanations about teachers, all of which are qualitative in nature.